How Demographic and Academic Factors Relate to Critical Thinking Skills among Indonesian Nursing Students - Gita Adelia; Esperanza Zuriguel P´erez; Eka Malfasari; Rizka Febtrina; Ulfa Hasana (Journal Of Nursing Practice, 2026)
Background: Critical thinking is a core competency for nursing students because it supports clinical judgment, evidence-based practice, and patient safety. However, evidence on critical thinking among nursing students in Indonesia remains limited, and findings on the influence of demographic and academic factors are inconsistent. Purpose: This study aimed to examine the relationship between demographic and academic characteristics and critical thinking levels among Indonesian nursing students. Methods: This cross-sectional study was conducted at the largest private health education institution in Riau Province, Indonesia. Of the 400 eligible students, 365 completed the survey, resulting in an analyzable response rate of 91.3%. Data were collected using the Nursing Critical Thinking in Students Questionnaire (N-CT-4 Students), which consists of 109 items across four dimensions of the 4-Circle Critical Thinking Model. Data were analyzed using descriptive statistics, the Kruskal–Wallis test, and the chi-square test of independence. Results: Nearly half of the respondents had a moderate level of critical thinking (48.2%). Inferential analysis showed that gender (χ² = 7.997; p = 0.018), educational program (χ² = 10.886; p = 0.004), academic year (χ² = 12.352; p = 0.015), and semester level (χ² = 12.352; p = 0.015) were significantly associated with critical thinking level. Age was not significantly associated with critical thinking level (H = 4.398; p = 0.111). Conclusion: Most nursing students demonstrated a moderate level of critical thinking. Critical thinking was associated with gender and academic characteristics, whereas age was not. Nursing educators may strengthen critical thinking through case-based, reflective, and structured clinical learning strategies across the curriculum.